PENGARUH PEMBERIAN SARI BUAH JAMBU BIJI (Psidium guajava Linn.) TERHADAP KADAR TRIGLISERIDA MENCIT BALB/c - Tanzillah Hame Peina Yosa; Kusdalinah Kusdalinah; Ahmad Rizal (JURNAL PENELITIAN TERAPAN KESEHATAN, 2020)
Abstract : Diabetes mellitus is caused by insulin resistance is disrupted so that the hormone sensitive lipase in adipose tissue will become active and lipolysis is increased, Psidium guajava is known to have a hypertriglyceride effect that can be useful. This study aims to determine the effect of Psidium guajava juice on triglyceride levels of BALB / c mice in induction of sucrose load. The research type is true-experiment with pretest-posttest with control group design. This research was conducted with 20 BALB / c mice which were given 10% sucrose for 15 days. The intervention was Psidium guajava with three dose variations: 0.25 ml / 20gBB, 0,50 ml / 20gBB and 1.00 ml / gBB for 7 days. Data analysis using one-way ANOVA test followed by post-hoc LSD test. The results showed that there were significant differences between treatment group X1 and treatment group X3. A significant decrease in triglyceride levels was found in the dose group of 1.00 ml/20 gBB with the dose group 0,25 ml/20gBB. It is recommended in subsequent research to identify the active compounds contained in Psidium guajava in providing health.Keywords: Diabetes mellitus, Triglycerides, Psidium guajava.